Karakteristik Wilayah Banjir Bandang di Sub DAS Batang Taluak Ambun Kabupaten Pasaman Barat - Aidil Kusuma; Azhary Syarief (Al-DYAS, 2026)
The Batang Taluak Ambun Sub-watershed in West Pasaman Regency is characterized by varied topography and high rainfall, making it vulnerable to flash flood hazards. This study aimed to identify and analyze the physical characteristics and to map the flash flood hazard levels in the area. A descriptive quantitative research design was employed, with the study site located in the Batang Taluak Ambun Sub-watershed and the samples consisting of land units determined through purposive sampling in accordance with the research objectives. The results showed that the physical characteristics of the area include slope gradients ranging from flat to very steep; annual rainfall of 2,000–2,500 mm, which is classified as high; dominant soil types consisting of haplic Oxisols, district Gleysols, and hydric alluvial soils with good drainage; and land use dominated by forest in highland areas and dryland agriculture in hilly regions. The analysis of flash flood hazard levels for each land unit in the Batang Taluak Ambun Sub-watershed indicated three classes: high hazard (prone) in land units F1, Qh, Swh, I, AvlH; F1, Qh, Pmk, I, GlsD; F1, Qh, Plk, II, OksH; and V8, Tmv, Pmk, I, OksH; medium hazard (moderately prone) in land units V8, Tmv, Pmk, OksH; V8, Tmv, Htn, III, OksH; V6, Tmv, Plk, III, OksH; and V5, Tmv, Plk, II, OksH; and low hazard (not prone) in land units V6, Tmv, Htn, III, OksH; V5, Tmv, Plk, II, OksH; and V4, Tmv, Htn, II, OksH. These findings confirm that the combination of steep topography, high rainfall, soil properties, and land-use patterns contributes to the heightened vulnerability to flash floods, thereby necessitating land and regional management that is more adaptive to hydrometeorological risks.